The Wanderer - Creech, Sharon (Scholastic, 2000)
Thirteen-year-old Sophie and her cousin Cody record their transatlantic crossing aboard the Wanderer, a forty-five foot sailboat, which, along with uncles and another cousin, is en route to visit their grandfather in England.